Phrenic Nerve Injury During Cryoballoon-Based Pulmonary Vein Isolation: Results of the Worldwide YETI Registry. (January 2022) - Heeger, Christian-H.; Sohns, Christian; Pott, Alexander; Metzner, Andreas; Inaba, Osamu; Straube, Florian; Kuniss, Malte; Aryana, Arash; Miyazaki, Shinsuke; Cay, Serkan; Ehrlich, Joachim R.; El-Battrawy, Ibrahim; et al.
Abstract : Background: Cryoballoon-based pulmonary vein isolation (PVI) has emerged as an effective treatment for atrial fibrillation. The most frequent complication during cryoballoon-based PVI is phrenic nerve injury (PNI). However, data on PNI are scarce. Methods: The YETI registry is a retrospective, multicenter, and multinational registry evaluating the incidence, characteristics, prognostic factors for PNI recovery and follow-up data of patients with PNI during cryoballoon-based PVI. Experienced electrophysiological centers were invited to participate. All patients with PNI during CB2 or third (CB3) and fourth-generation cryoballoon (CB4)-based PVI were eligible. Results: A total of 17 356 patients underwent cryoballoon-based PVI in 33 centers from 10 countries. A total of 731 (4.2%) patients experienced PNI. The mean time to PNI was 127.7±50.4 seconds, and the mean temperature at the time of PNI was −49±8°C. At the end of the procedure, PNI recovered in 394/731 patients (53.9%). Recovery of PNI at 12 months of follow-up was found in 97.0% of patients (682/703, with 28 patients lost to follow-up). A total of 16/703 (2.3%) reported symptomatic PNI. Only 0.06% of the overall population showed symptomatic and permanent PNI. Prognostic factors improving PNI recovery are immediate stop at PNI by double-stop technique and utilization of a bonus-freeze protocol. Age, cryoballoon temperature at PNI, and compound motor action potential amplitude loss >30% were identified as factors decreasing PNI recovery. Based on these parameters, a score was calculated. The YETI score has a numerical value that will directly represent the probability of a specific patient of recovering from PNI within 12 months. Conclusions: The incidence of PNI during cryoballoon-based PVI was 4.2%. Overall 97% of PNI recovered within 12 months. Symptomatic and permanent PNI is exceedingly rare in patients after cryoballoon-based PVI. The YETI score estimates the prognosis after iatrogenic cryoballoon-derived PNI. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03645577. Graphic Abstract: A graphic abstract is available for this article. Abstract : Supplemental Digital Content is available in the text.